AGAMA DAN KESALEHAN EKONOMI: Sebuah Potret Realitas di Kalangan Masyarakat Surabaya - Djakfar, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2007)
Along with the industrialization policy in the New Order era, city expansion was a certainty. As a result, rural communities began to change significantly. The changes included economic activity patterns. In short, development as the New Orders jargon and symbol of progress has resulted in the collapse of the established rural traditional social structures. Suralaya community, as a part of the outskirts of Betawi, axperiences the same thing as the other parts of Betawi as a whole. It gets the effect of industrial area and city axpansion. The demographical and geographical pressures from Jakarta and Tangerang and Governmants industrialization policy really have long-term impact on Suralaya community. In facing such condition, Betawi society who devote their lives to their religion, that is, Islam, make the religion as basic identity because Islamic teachings give them feeling of pride and safe protection from any threats. Nevertheless, we have to consider that in reality, religion is not the only determiningfactor. We are sure that religion is only one of the factors that influence human behavior, and that religion itself is also influenced by the material condition of a society. However, we have to acknowledge that religion reflects on the traders daily behavior, together with their experiences, spirit, talents, and struggles in their business. We can see those from the way they interpret the religious symbols in relation to their daily business activities.